Understanding Generation Z in the Workplace: Characteristics, Challenges, and Implications - Nugrohojati, Ihsan Satrio; Linando, Jaya Addin (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2025)
The purpose of this study is to identify and analyze the career development of Generation Z. In addition, another objective of this study is to explore the application of career development to Generation Z employees. Using a qualitative approach, this study employed phenomenological methods to conduct in-depth interviews with six respondents working in companies in Indonesia. The results of this study suggest that the characteristics of Generation Z encompass both its advantages and disadvantages, as well as the challenges it faces. There are limitations in terms of time, energy, and the researcher's ability in this research. For further research, it is recommended to explore career development in Generation Z in various aspects. In addition, quantitative research can be used to measure the career development of Generation Z in detail.